2020
DOI: 10.1007/s00259-020-05018-z
|View full text |Cite|
|
Sign up to set email alerts
|

Higher thyroid hormone levels and cancer

Abstract: Purpose This narrative review aims to summarize the relationship between hyperthyroidism, upper reference range thyroid hormone (TH) levels, and cancer, and to address the clinical management of hyperthyroidism in cancer patients. Methods A comprehensive search was performed by an independent reviewer through Google Scholar and PubMed Electronic databases. All searches were restricted to English language manuscripts published between 2000 and 2020.Results Numerous in vitro, in vivo, and population-based studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 66 publications
0
18
0
2
Order By: Relevance
“…Notably, VEGFR‐TKI‐induced thyroid dysfunction may be associated with the prognosis of cancer 9‐11 . The onset of hypothyroidism is usually accompanied by improved prognosis, while the onset of hyperthyroidism is usually accompanied by poor prognosis 10,12 . Therefore, it is necessary to better understand VEGFR‐TKI‐induced thyroid dysfunction, to ensure the prompt diagnosis and appropriate management of the condition.…”
Section: What Is Known and Objectivementioning
confidence: 99%
See 1 more Smart Citation
“…Notably, VEGFR‐TKI‐induced thyroid dysfunction may be associated with the prognosis of cancer 9‐11 . The onset of hypothyroidism is usually accompanied by improved prognosis, while the onset of hyperthyroidism is usually accompanied by poor prognosis 10,12 . Therefore, it is necessary to better understand VEGFR‐TKI‐induced thyroid dysfunction, to ensure the prompt diagnosis and appropriate management of the condition.…”
Section: What Is Known and Objectivementioning
confidence: 99%
“…accompanied by improved prognosis, while the onset of hyperthyroidism is usually accompanied by poor prognosis. 10,12 Therefore, it is necessary to better understand VEGFR-TKI-induced thyroid dysfunction, to ensure the prompt diagnosis and appropriate management of the condition. However, there is a lack of systematic investigations evaluating the effects of VEGFR-TKIs on thyroid dysfunction in real-world settings.…”
mentioning
confidence: 99%
“…Similarly, the experimental induction of a hypothyroid state in mice affected by either spontaneous or xenografted human tumors was often shown to reduce the rate of cancer growth [ 239 ]. Moreover, it has been reported that high free T4 (FT4) levels are associated with an increased risk of any solid, lung, and breast cancer [ 242 , 243 ], and that hypothyroidism is associated with an older age of onset of different kinds of cancer (for example, breast and lung cancers) [ 244 , 245 , 246 ]. In the case of breast cancer, an effect of T3 on cancer cell motility has also been reported [ 106 ].…”
Section: Thyroid Hormones and Brain Cancermentioning
confidence: 99%
“…In Section 2.2 , we reported that THs, after binding to αvβ3 integrin, can activate intracellular kinases via the MAPK/ERK1/2 pathways, thus stimulating cell proliferation. This ability might have a role in different cancer types [ 100 , 103 , 104 , 105 , 106 , 245 ], also because malignant cells express higher amounts of αvβ3 integrin when compared with normal cells [ 105 ]. Notably, activation of these pathways affects transcription of a variety of genes encoding proteins involved in different aspects of cancer, such as signal transduction, angiogenesis, regulation of cytoskeleton dynamics, and epithelial–mesenchymal transition [ 104 , 105 , 106 ].…”
Section: Thyroid Hormones and Brain Cancermentioning
confidence: 99%
“…Thyroid hormones may play a significant role in carcinogenesis and disease progression. However, the clinical impact of thyroid hormones in different cancer entities is not uniform [4]. Several in vitro studies investigated the effects of thyroid hormones on different cancer cell lines.…”
Section: Introductionmentioning
confidence: 99%